2018
DOI: 10.3389/fphar.2018.00264
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Use During Pregnancy and Lactation: A Case-Series Report

Abstract: The current prescription of clozapine in psychotic women of reproductive age makes it crucial to understand its pharmacokinetics during pregnancy and lactation as well as its risk profile for neonatal outcome. The aim of this case series was to provide new evidence on the pharmacokinetic features of clozapine that determine its passage through the placenta and amniotic fluid, as well as the neonatal clozapine elimination half-life (t1/2). This case series demonstrates for the first time that clozapine might sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…With respect to clozapine in breast milk, the potential risks for infants are largely unknown. Imaz and coworkers 66 did not find any acute toxicological effect in newborns exposed to clozapine in pregnancy. The alternative in women who are unresponsive to other antipsychotic drugs is stopping antipsychotic treatment altogether and this, of course, confers risks of its own.…”
Section: Postpartum Psychotic Disordersmentioning
confidence: 92%
“…With respect to clozapine in breast milk, the potential risks for infants are largely unknown. Imaz and coworkers 66 did not find any acute toxicological effect in newborns exposed to clozapine in pregnancy. The alternative in women who are unresponsive to other antipsychotic drugs is stopping antipsychotic treatment altogether and this, of course, confers risks of its own.…”
Section: Postpartum Psychotic Disordersmentioning
confidence: 92%
“…The treatment generally includes sequential administration of short-term benzodiazepines, antipsychotics, and lithium, with response monitoring. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Cases of long-term treatment-resistant psychoses with onset during the postpartum period have been reported and a few studies have explored the efficacy of electroconvulsive therapy, but data sustaining the best therapeutic attitude for these cases is lacking. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…The F:M concentration ratios of clozapine, the first atypical antipsychotic developed, varied from 0.39 to 0.58, as reported by Imaz et al, whereas Barnas et al found a much higher value of 1.91. 80,81 These values result in a geometric mean of 0.64 (n = 5). The active metabolite of clozapine, norclozapine, has F:M concentration ratios ranging between 0.21 and 0.37 (geometric mean = 0.29, n = 4).…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%